Color and Empathy : Essays on Two Aspects of Film - Brinckmann, Christine, 1937- (Book collections on Project MUSE., 2014)
This book focuses on two areas of interest: the poetics of color in film and the affective responses of viewers. Each essay is built around the analysis of a particular film or group of related films, which are then used to explore a range of issues including the difference between black-and-white and color, the emergence of bold color schemes in the 1950s, and empathetic viewer reactions to fictional characters, documentary subjects, animals, and architecture in film.